Eldfellite-type cathode material, NaV(SO4)2, for Na-ion batteries. Issue 18 (13th July 2022) - Nishio, Akira; Ishado, Yuji; Nakamoto, Kosuke; Kobayashi, Eiichi; Inoishi, Atsushi; Sakaebe, Hikari; Okada, Shigeto
Abstract : A novel eldfellite-type cathode material, NaV(SO4 )2, demonstrates a reversible capacity of 102 mA h g −1 with the two-step charge–discharge reaction. Abstract : In this research, an eldfellite-type material containing V as a transition metal, NaV(SO4 )2, was investigated to achieve higher potentials and capacities through the use of a multi-redox pair. Average working potentials of 3.9 and 2.1 V vs. Na/Na + were observed, and a large reversible capacity of 102 mA h g −1 was obtained over a wide potential range. Moreover, X-ray absorption near-edge structure and near-edge X-ray absorption fine structure measurements revealed that only V contributes to the charge compensation in the sodiation/desodiation process at low potentials, whereas both V and O contribute to the desodiation/sodiation process at high potentials. This phenomenon was also supported by the density of states and Bader charge analysis based on the DFT calculations.